2019
DOI: 10.1002/glia.23681
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Contactin multi‐molecular complex secreted by oligodendrocytes in nodal protein clustering in the CNS

Abstract: The fast and reliable propagation of action potentials along myelinated fibers relies on the clustering of voltage‐gated sodium channels at nodes of Ranvier. Axo‐glial communication is required for assembly of nodal proteins in the central nervous system, yet the underlying mechanisms remain poorly understood. Oligodendrocytes are known to support node of Ranvier assembly through paranodal junction formation. In addition, the formation of early nodal protein clusters (or prenodes) along axons prior to myelinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 62 publications
1
45
0
Order By: Relevance
“…The occurrence of evenly spaced clusters of nodal components along axons prior to myelination, initially reported on retinal ganglion cells (Kaplan et al, 2001(Kaplan et al, , 1997 was also observed in vitro and in vivo on GABAergic hippocampal neurons, but not on pyramidal hippocampal neurons (Bonetto et al, 2019;Dubessy et al, 2019;Freeman et al, 2015). These early clusters, which share features with nodes of Ranvier (identical subunits β1Nav and β2Nav have been shown to play critical roles in modulating the membrane density and the function of αNav (Chen et al, 2002;Kazen-Gillespie et al, 2000;O'Malley and Isom, 2015;Patton et al, 1994).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…The occurrence of evenly spaced clusters of nodal components along axons prior to myelination, initially reported on retinal ganglion cells (Kaplan et al, 2001(Kaplan et al, , 1997 was also observed in vitro and in vivo on GABAergic hippocampal neurons, but not on pyramidal hippocampal neurons (Bonetto et al, 2019;Dubessy et al, 2019;Freeman et al, 2015). These early clusters, which share features with nodes of Ranvier (identical subunits β1Nav and β2Nav have been shown to play critical roles in modulating the membrane density and the function of αNav (Chen et al, 2002;Kazen-Gillespie et al, 2000;O'Malley and Isom, 2015;Patton et al, 1994).…”
Section: Introductionmentioning
confidence: 86%
“…Whether they might be linked to neuronal electrical activity or to locally secreted factors is still to be characterized. The fact that early nodelike clustering also depends on oligodendroglial secreted cues (Dubessy et al, 2019;Freeman et al, 2015;Kaplan et al, 2001Kaplan et al, , 1997 further shows that a tightly regulated dual interaction between neuron and glia is required for myelinated fiber organization.…”
Section: Early Clusters Participate In Node Of Ranvier Formationmentioning
confidence: 98%
See 2 more Smart Citations
“…However, stronger effects were demonstrated in the case of neural adhesive glycoproteins provided with key relevant regulatory roles in neural developmental control as is typically the case for Contactin family components [ 77 ] and in particular for Contactin 1 [ 55 , 78 ], for which a stronger downregulation, accounting to about 50% was demonstrated in the dorsal horn. This Contactin 1 behavior could be explained based on its cell type-specificity, which, besides the neuronal lineage, also concerns the glial, in particular the oligodendrocyte lineage in which it participates to the mechanism of myelination through its effects on nodal/paranodal regions organization [ 55 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%